Cost of high leverage in socially responsible firms in a linear dynamic panel model. Evidence from product market interactions - Zeeshan Ahmed; Qasim Saleem; Muhammad Maroof Ajmal; Hajra Jameel (Heliyon, 2022)
Corporate Social responsibility is the major challenge for senior management of firms and they devoted the significant resources for CSR initiatives. Despite of significant comprehension of CSR, an ongoing debate is still under consideration about its economic repercussions in terms of “do well by doing good”. Corporations are facing huge leverage cost with bad customer reputation in the product market. This study attempt to examine this phenomenon as the cost of high leverage in socially responsible firms and the product market interactions of those firms. The data is collected from 2009-2020 in linear dynamic setting for product market interaction, and two step system GMM estimation technique is applied for endogeneity concerns. The study identified that socially responsible firms are experiencing better growth in their sales in product market that maximize the financial benefits. However, the high leverage cost worsen their performance in product market because leverage is associated with some losses in market share due to unfavorable actions of competitors and customers. Socially responsible firms experience the low cost of high leverage which helps the firms to increase the performance in product market. Moreover, the corporate governance effectively devises the strategies to diminish the high leverage cost in the way towards better product market interactions. The results are conclusive across the financial crisis, firm’s classifications and different channels of firms. The study enables the holistic and broader understanding of CSR in the reduction of high leverage cost with an intention to increase the firm’s sustainability in product market. The study contributes with a view to ascertain the cost of high leverage in socially responsible firms for product market interactions of Pakistani firms in a linear dynamic panel.